Psychometric properties of the Dutch extended Cancer Survivors' Unmet Needs measure (CaSUN‐NL). (22nd January 2018) - Keeman, M.C.; Bolman, C.A.W.; Mesters, I.; Willems, R.A.; Kanera, I.M.; Lechner, L.
Abstract : Information and support needs increase emotional distress and can impede cancer survivors' adjustment. To investigate the information and support needs of Dutch cancer survivors, the Cancer Survivors' Unmet Needs measure (CaSUN) was translated into Dutch and applied in two Dutch studies with cancer survivors ( N  = 255; N  = 467). The CaSUN‐NL entailed the original five CaSUN scales, extended with respectively a returning to work and lifestyle scale. This study aimed to determine the psychometric properties of the CaSUN‐NL. To assess validity, a maximum likelihood factor analysis was employed. Construct validity was analysed using Pearson's and Spearman's correlation coefficients. To assess reliability, test–retest (Kappa coefficient) and internal consistency (Cronbach's alpha) values were determined. Factor analysis revealed the original five factors. Test–retest reliability was low ( r  ≤ .15, 93% retest response). Internal consistency values were high (Cronbach's alpha = 0.92–0.94), except for lifestyle. Significant correlations were found between total number of unmet needs with anxiety ( r  = .55), depression ( r  = .49), negative adjustment ( r  = .50), quality of life ( r  = −.52) and age ( r  = −.24). The CaSUN‐NL is valid and reliable to investigate the unmet information and support needs of Dutch cancer survivors.